Planning of Solar Generation for Renewable Energy Development in the Evironment of Univeritas Siliwangi, Campus II Mugasari - Linda Faridah; M Aris Risnandar; Rian Nurdiansyah (Journal of Electrical, Electronic, Information, and Communication Technology, 2024)
The utilization of renewable energy, particularly solar energy, is becoming increasingly crucial in efforts to reduce dependence on fossil fuels and mitigate the impacts of climate change. Higher education institutions play a vital role in adopting and promoting clean energy technologies. This research aims to plan the implementation of a solar power generation system (PLTS) at Siliwangi University Campus II Mugasari using Helioscope software-based simulation. The research methodology includes topographical analysis of the location, evaluation of solar energy potential, and optimization of system design to maximize efficiency and energy output. Helioscope was chosen for its ability to model photovoltaic systems by considering critical variables such as solar radiation, panel configuration, and specific location characteristics. Simulation results indicate that the designed PLTS system has significant potential in generating electrical energy and contributing to the reduction of greenhouse gas emissions. Quantitative analysis includes estimates of energy production capacity, optimal configuration of photovoltaic arrays, and long-term system performance projections. This research provides a comprehensive blueprint for developing renewable energy infrastructure in the campus environment. Additionally, this study contributes to the body of knowledge related to the integration of solar technology in academic contexts and can serve as a replicable model for other higher education institutions in transitioning towards more sustainable and environmentally friendly campuses. Keywords: Renewable Energy, Helioscope, Solar Power Generation System (PLTS), Siliwangi University.